PERTUMBUHAN JAMUR KUPING (AURICULARIA POLYTRICA) PADA DELAPAN JENIS KAYU - Sihati Suprapti; Ginuk Sumarni (Jurnal Penelitian Hasil Hutan, 1987)
Ear mushroom (Auricularia  polytrica)  was cultivated on logs of eight wood species i.e.  hamerang (Ficus grossularoides  Burn. f.), jeungjing (Albizia falcataria  (L.)  Fosb.), kihuut (Vernonia arborea  Ham.),  kipiit  (Maesa ramentacea  Wall.), manii (Maesopsis eminii Engl.),  sehang (Ficus padana Burn. f.), seuseureuhan  (Piper aduncum  L.)  and teureup (Artocarpus  elastica Reinw. ). The logs were kept slanted on an angle of  ± 60° with bamboo  supports  in shady site under trees at Gunung  Bunder,  Bogor.The mature mushroom  was harvested  every day after  the growth  of  the fruiting body.   The logs start producing fungus two months after inoculation. The highest harvested  was obtained  at fourth   month  of observation.  The higher total yield of ear mushroom  during  the six months observation  was obtained from  seuseureuhan  log (59.537 kg), sehang (28.08 kg), manii (16.056 kg) and hamerang log (14.838 kg) per m3 of log. The lower total yield  was obtained from  kipiit  log (11.2 kg), kihuut  (9.813 kg), jeungjing  (4.526 kg) and teureup (2.441 kg) per  m3 of log.